2017
DOI: 10.3389/fneur.2017.00502
|View full text |Cite
|
Sign up to set email alerts
|

Preferential Impairment of the Contralesional Posterior Semicircular Canal in Internuclear Ophthalmoplegia

Abstract: BackgroundThe vertical vestibulo-ocular reflex (VOR) may be impaired in internuclear ophthalmoplegia (INO) as the medial longitudinal fasciculus (MLF) conveys VOR-signals from the vertical semicircular canals. It has been proposed that signals from the contralesional posterior semicircular canal (PSC) are exclusively transmitted through the MLF, while for the contralesional anterior canal other pathways exist.ObjectiveHere, we aimed to characterize dysfunction in individual canals in INO-patients using the vid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 30 publications
2
10
0
Order By: Relevance
“…Our findings in PLW-MS, nearly all of whom had clinical evidence of brainstem involvement, are in agreement with the extend prior studies that reveal a similar pattern of graduated involvement of the lateral, anterior, and posterior SCC pathways in adults who have evidence of INO associated with medial longitudinal fasciculus lesions on magnetic resonance imaging [ 23 , 24 ]. In a cohort of adults with brainstem infarcts or demyelination that was associated with INO, the results, which were obtained from a vHIT system not unlike the system we used, revealed that a VOR gain reduction was more pronounced for the contralesional posterior SCC than the ipsilateral lateral and anterior SCCs in unilateral INO [ 24 ]. It is of note that PLW-MS who have either unilateral or bilateral INO have been shown to have asymmetrical ipsilesional VOR deficits and that the VOR gain is lower for the adducting compared to the abducting eye when the eye movement is measured binocularly using search coils [ 23 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our findings in PLW-MS, nearly all of whom had clinical evidence of brainstem involvement, are in agreement with the extend prior studies that reveal a similar pattern of graduated involvement of the lateral, anterior, and posterior SCC pathways in adults who have evidence of INO associated with medial longitudinal fasciculus lesions on magnetic resonance imaging [ 23 , 24 ]. In a cohort of adults with brainstem infarcts or demyelination that was associated with INO, the results, which were obtained from a vHIT system not unlike the system we used, revealed that a VOR gain reduction was more pronounced for the contralesional posterior SCC than the ipsilateral lateral and anterior SCCs in unilateral INO [ 24 ]. It is of note that PLW-MS who have either unilateral or bilateral INO have been shown to have asymmetrical ipsilesional VOR deficits and that the VOR gain is lower for the adducting compared to the abducting eye when the eye movement is measured binocularly using search coils [ 23 ].…”
Section: Discussionsupporting
confidence: 92%
“…In response to lateral head impulses, PLW-MS have been shown to recruit CSs less often and with a slightly longer latency than persons who are status-post unilateral vestibular deafferentation [ 19 ] but more often with a reduced latency relative to healthy controls [ 21 , 22 ]. PLW-MS who have documented infratentorial lesions [ 23 , 24 ] and with suspected occult [ 18 ] internuclear ophthalmoplegia (INO) are reported to have asymmetrical abnormal VOR gains.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter is a combination of skew deviation, contralateral head tilt and ocular torsion, and reflects dysfunction of vestibular reactions in the roll plane ( 11 ). The role of the MLF in carrying exclusively contralateral posterior semicircular canal signals is confirmed by studies that combine MRI and the video-head-impulse test ( 12 ). Patients with unilateral INO may have vertical diplopia due to a non-evident skew deviation, which can be relieved by using a small vertical prism.…”
Section: Eye Movement Disorders In Msmentioning
confidence: 91%
“…[55][56][57] Among these, upbeat, seesaw nystagmus, and contraversive OTR and SVV tilt and impairment of the vertical VOR may occur as well as abnormal cervical and ocular VEMP responses. [55][56][57] Ten patients with INO due to strokes showed a prominent decrease in the VOR gain for the contralesional posterior canal during HITs. 55 The MLF may serve as the pathway for high acceleration VOR from the contralateral posterior canal.…”
Section: Development Ofmentioning
confidence: 99%